2020
DOI: 10.1186/s13058-020-01344-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts direct differentiation of human breast epithelial progenitors

Abstract: Background Breast cancer arises within specific regions in the human breast referred to as the terminal duct lobular units (TDLUs). These are relatively dynamic structures characterized by sex hormone driven cyclic epithelial turnover. TDLUs consist of unique parenchymal entities embedded within a fibroblast-rich lobular stroma. Here, we established and characterized a new human breast lobular fibroblast cell line against its interlobular counterpart with a view to assessing the role of region-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…Moreover, close inspection of the fibroblast population (cluster 1) indicated that a lower proportion of cells expressed key marker genes such as PDGFRA, PDGFRB, CD34, and the matrix‐associated genes POSTN and COL3A1 (also SPARC, COL5A2, COL14A1 ) in post‐menopausal tissue (Fig 3A). High‐resolution confocal imaging of breast tissue to address expression and spatial distribution indicated a marked decrease in PDGFRβ+ fibroblasts in post‐menopausal tissue (Fig 3B), including the interlobular fibroblasts (Morsing et al, 2020). Some variation between post‐menopausal tissue sections was apparent, in part reflecting the regression of TDLUs.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, close inspection of the fibroblast population (cluster 1) indicated that a lower proportion of cells expressed key marker genes such as PDGFRA, PDGFRB, CD34, and the matrix‐associated genes POSTN and COL3A1 (also SPARC, COL5A2, COL14A1 ) in post‐menopausal tissue (Fig 3A). High‐resolution confocal imaging of breast tissue to address expression and spatial distribution indicated a marked decrease in PDGFRβ+ fibroblasts in post‐menopausal tissue (Fig 3B), including the interlobular fibroblasts (Morsing et al, 2020). Some variation between post‐menopausal tissue sections was apparent, in part reflecting the regression of TDLUs.…”
Section: Resultsmentioning
confidence: 99%
“…23 Similarly, functionally heterogeneous fibroblasts in the normal breast have been described. 24 Epithelial cell types were dominant. Using CD49f/EpCAM expression pattern as well as TP63/NFIB, ELF5/EHF, and FOXA1/ESR1 as functional markers of basal/stem, luminal progenitors, and mature luminal cells, we performed subcluster analyses of epithelial cells, which revealed 13 different epithelial cells (Figures 1B and 1C).…”
Section: Epithelial Cell Clusters Of the Normal Breastsmentioning
confidence: 99%
“…Because our study involved breast biopsies of healthy women, tissue is very limited in quantity, and breast-region-specific differences in the cell types could not be ascertained. Recent studies have identified different biology and marker profiles in Article ll fibroblasts of the ductal and lobular regions of the breast, 24 and it will not be a surprise if transcriptome of epithelial cells in the ductal and lobular regions are different, which the current approaches cannot address. Lastly, it is difficult to account for inter-individual differences in transcriptome due to genetic diversity in the human population.…”
Section: Gene Signatures Of Epithelial Clusters and Their Relevance To Breast Cancermentioning
confidence: 99%
“…Notably, this analysis 274 also revealed a transition from a more luminal-like state in normal samples to a more 275 mesenchymal-like state in synchronous DCIS that aligned with analogous shifts in tumor 276 cell differentiation and function ( Figure 4I). In light of previous studies revealing a functional and structural interdependence between myoepithelium and the surrounding stroma (Jones et al, 2003;Morsing et al, 2020), we next sought to determine if the progressive loss of myoepithelial integrity observed here correlated with changes in fibroblast function and extracellular matrix remodeling (ECM). Single cell clustering revealed four fibroblast populations that included normal (CD36 high), resting (VIM-only), myofibroblast (SMA + ), and CAF (FAP + ) subsets ( Figure 5A).…”
Section: Myoepithelial Breakdown and Phenotypic Change During Dcis Prmentioning
confidence: 99%